Enterobacter-activated mosquito immune responses to Plasmodium involve activation of SRPN6 in Anopheles stephensi. - Abraham G Eappen; Ryan C Smith; Marcelo Jacobs-Lorena (PLoS ONE, 2013)
Successful development of Plasmodium in the mosquito is essential for the transmission of malaria. A major bottleneck in parasite numbers occurs during midgut invasion, partly as a consequence of the complex interactions between the endogenous microbiota and the mosquito immune response. We previously identified SRPN6 as an immune component which restricts Plasmodium berghei development in the mosquito. Here we demonstrate that SRPN6 is differentially activated by bacteria in Anopheles stephensi, but only when bacteria exposure occurs on the lumenal surface of the midgut epithelium. Our data indicate that AsSRPN6 is strongly induced following exposure to Enterobacter cloacae, a common component of the mosquito midgut microbiota. We conclude that AsSRPN6 is a vital component of the E. cloacae-mediated immune response that restricts Plasmodium development in the mosquito An. stephensi.